Research in the Development and Validation of the Method of Quantitative Determination of Flavonoids in the Common Sorrel Herba, Gathered in the Altai Territory - G. R. Kutateladze; L. M. Fedoseeva (Разработка и регистрация лекарственных средств, 2019)
Introduction. Common sorrel (Rumex acetosa L.) is a biennial herb from the Buckwheat family (Polygonaceae L.). In our previously studies of phenolic compounds composition of alcohol extraction and ethereal, ethyl acetate, butanol fractions of common sorrel herba and flavonoids of the flavonol group was found. From the literature sources it is known that flavonoids are one of the groups of biologically active compounds with anti-inflammatory action. In this regard, the actual task is to assess the quantitative content of flavonoids in common sorrel herba.Aim. Is the development and validation of a method for the quantitative determination of flavonoids in common sorrel herba.Materials and methods. It has been established that the flavonoid complex of common sorrel herba includes rutin, therefore, the reference sample (RS) rutin was used as a standard for calculating the amount of flavonoids. Alcohol extract of common sorrel herba and a solution of rutin RS were prepared. The complexation reaction with aluminum chloride was carried out. The resulting solutions were investigated by the method of differential spectrophotometry. The spectral characteristics of the test and standard samples were compared. Then we studied the effect of extraction conditions on the yield of flavonoids from the raw material: the extractant, the particle size of the raw material, the ratio of «raw material – extractant», temperature, frequency and duration of extraction. Purified water and ethyl alcohol of various concentrations (20%, 40%, 70%, 90%) were used as the extractant. Next, carried out the selection of the optimal conditions for the complexation reaction (the complexation reaction time, the ratio of «aliquot – aluminum chloride alcohol solution»). The method was validated according to GPM.1.1.0012.15 of the State Pharmacopoeia (SF) XIII edition and generally accepted methods for the following indicators: specificity, analytical field, linearity, accuracy, precision.Results and discussion. The optimal parameters for extracting flavonoids from raw materials were determined (threefold extraction with ethyl alcohol 70% in a water bath, the ratio of «raw material – extractant» – 1:30 for 30 minutes, the particle size of the raw material – 2.0 mm). The conditions for the complexation reaction were selected (the ratio «aliquot: aluminum chloride alcohol solution» – 1: 2.5, the complexing agent – aluminum chloride solution 5% alcohol, the appearance of a stable solution color after 40 minutes). When carrying out the validation of the developed method, it was established that the validation characteristics under study are within the acceptance criteria. When analyzing the raw materials harvested in the Altai Territory in different years, it was found that the content of flavonoids in common sorrel herba ranges from 0,596 to 0,632%.Conclusion. The optimal parameters of extraction of flavonoids from raw materials were determined, the conditions for the complexation reaction were selected, and the developed method was validated. The quantitative content of flavonoids in terms of rutin in sorrel sour grass harvested in the Altai Territory in different years has been established.